Various Symptoms, Prevention and Treatments of Corona-virus (Covid-19) - Jadhao, Amol G.; Magar, Vaishali B. (Asian Journal of Pharmaceutical Research and Development, 2021)
Corona means “crown,” and examined nearly, the round virus has a “crown” of proteins called peplomers jutting out from its center in every direction. These proteins help the virus identify whether it can infect its host. The severe acute respiratory syndrome has caused an alarmimg situation of the worldwide. The first detection, in Decmber2019, there have been no effective drug therapy options for treating the SARS-CoV-2 pandemic. And healthcare professionals are using some drug like remdesivir, favipiravir, chloroquine, hydrochloroquine, azithromycin, paracetamol, steroids, multivitamins, ivermectin, tocilumab, NSAIDs, treatment with monoclonal antibodies and convalescent plasma etc. of treatments. The condition known as severe acute respiratory syndrome (SARS) was also linked to a highly infectious coronavirus. The SARS virus has since been included and found to be successfully curable. The disease is caused by the virus severe acute respiratory syndrome coronavirus 2 (SARS-CoV- 2), previously referred to as the 2019 novel coronavirus (2019-nCoV). The symptoms is typically rapid, ranging from hours to days after infection. Symptoms include fever, cough and, often, sore throat, headache, Sneezing, shortness of breath, wheezing, or difficulty in breathing. Reduce their anxiety level effectively when they are in the events of stress by using reasonable coping styles. Early studies of the out-break focused on the novel coronavirus gene and structure modeling, host and clinical case analysis. Currently, hundreds of registered clinical trials are underway, most of which are assessing antiretroviral agents, anti-inflammatory or immunosuppressant therapies, and passive antibody treatments.